Idealised modelling of offshore-forced sea level hot spots and boundary waves along the North American East Coast. (November 2020) - Wise, Anthony; Polton, Jeff A.; Hughes, Chris W.; Huthnance, John M.
Abstract: Hot spots of sea level variability along the North American East Coast have been shown to shift in latitude repeatedly over the past 95 years and connections with a number of forcing phenomena, including the North Atlantic Oscillation (NAO) and Atlantic Meridional Overturning Circulation (AMOC), have been suggested. Using a barotropic 1/12° NEMO model of the North American East Coast (to represent the upper ocean and a homogeneous shelf), we investigate the coastal sea level response to remote sea surface height (SSH) variability along the upper continental slope. Hilbert transform Complex EOF analysis is used to investigate the responses to interannual changes in the strength of the mean winds and an idealised NAO. Variability in the mean winds produces in-phase coastal sea level variability along the entire coastline and is driven by a SSH anomaly in the subpolar gyre. Variability due to the NAO forcing is in phase along the coast south of Cape Hatteras. Interannual coastal sea level variability at a given latitude is found to be driven by off-shore SSH anomalies originating many degrees of latitude ( ∼ 100s km) further north, and linear barotropic trapped wave theory is used to explain the mechanism. A comparison of the results from an analytical model with those from the numerical model is used to suggest that the boundary wave mechanism is also relevant for understanding the coastal response to interior sea level change over longer time periods. Nonlinear effects are found not to significantly modify the character of the linear solution. Highlights: US east coast sea level rise hotspots driven by variability at higher latitudes. Location of sea level variability hotspots linked to boundary wave propagation. Deep ocean variability penetrates towards the coast with equatorward displacement. Subpolar gyre variability and NAO consistent with US east coast sea level change. Nonlinear effects do not significantly modify linear barotropic ocean-to-coast response.